Comparative study on pregnancy complications: PGT-A vs. IVF-ET with gender-specific outcomes - Guo, Ling; Li, Xiao; Guo, Anliang; Wang, Yufeng; Liang, Yue; Li, Yan; Xu, Xinbo; Lv, Hong (Frontiers in Endocrinology, 2024)
The safety and clinical effectiveness of preimplantation genetic testing for aneuploidy (PGT-A) in improving pregnancy outcomes for sub-fertile patients remains controversial. Potential sex-based differences in the relationship between PGT-A and pregnancy complications have not been investigated, which could guide the appropriate clinical application of PGT-A. In this secondary analysis of data from a multicenter, randomized, controlled, non-inferiority trial (NCT03118141), 940 women who achieved singleton live birth during the trial were included to estimate the between-group differences in pregnancy complications following PGT-A versus conventional in vitro fertilization (IVF) vary with fetal sex. Logistic regression analysis was used to adjust for possible confounders, and subgroup analysis was also performed. Among male fetuses, the risk of maternal preeclampsia was significantly lower after PGT-A compared to conventional IVF treatment (3.37% vs. 7.88%; adjusted OR, 0.40; 95% CI, 0.17-0.92; P = 0.032). However, this protective effect was not observed in pregnancies with female fetuses (3.63% vs. 3.38%; adjusted OR, 1.04; 95% CI, 0.36-3.00; P = 0.937). In addition, no significant sex-dependent differences in the risks of other pregnancy complications or neonatal outcomes were detected between PGT-A and conventional IVF groups (P > 0.05). In summary, PGT-A was associated with a decreased risk of maternal preeclampsia in singleton pregnancies with PGT-A reduces the risk of preeclampsia male fetuses, highlighting its potential utility in preeclampsia prevention in addition to spontaneous abortion rate reduction.